Tecnologia educacional e experimentação docente: um desafio necessário - Santos, Simone Francisco dos (2018)
The present dissertation, denominated Educational Technology and teaching experimentation: a necessary challenge, linked to the research line Language: Linguistic, Cultural and Teaching Practices, of the Masters in Letras of the Universidade Estadual do Oeste do Paraná – UNIOESTE has as its theme the Agrinho Program and his contributions related to Teaching Experimentation in municipal rural schools. In its initial part, we present the history of the Agrinho Program and its pedagogical proposal based on the transdiciplinary vision. We seek to observe if teachers have knowledge related to the possibilities of work based on the essence that the Agrinho Program brings in its conception and in its form to present the subjects to be worked. From this observation, we elaborate comments with the objective of contributing to the importance of the constant reflection on the teaching practice or Teaching Experimentation (according to Deleuze, 2006). Based on the above, the research sought to answer, mainly, the following questions: The methodological proposals of Agrinho present the clarity necessary to the understanding and acceptance by the teachers and are so that they are well used by them in the daily of the pedagogical doing? How is Pedagogical Experimentation or Teaching processed? What elements should a training program present to contribute to the improvement of educational quality? What points of the Agrinho Program facilitate the clear inference of the goals of the program by the educators, so that it is incorporated immediately to the teaching experimentation? Our research was carried out in the format of the Interpretative Qualitative Research, within the theoretical perspective of Applied Linguistics and Action Research, considering that there is participation and interference of the researcher, since in the year 2017, it began to work as support technical and pedagogical at the Municipal Department of Education, also assuming the role of director of rural schools. The theoretical basis of this research is supported by scholars such as Deleuze (2006), Guattari (2006), Delors (2000), Dal Molin (2003), Gallo (2002), Guattari (1990), Morin (2000), Nicolescu (2000), among others. The research contributed to identify the need to reorganize the distribution of educational programs available in the municipality, so that adherence to one of the programs is a teaching obligation, already known at the time of class distribution. In this way, we believe that teachers can better prepare themselves to apply the suggested methodological proposals, carrying out the Teaching Experimentations with greater support of the pedagogical coordination of the schools and of the Municipal Department of Education, aiming at a better appropriation of the opportunities made possible by the Agrinho Program.